COVID-19 school closures turning a spotlight on inequities and other shortcomings from the voices of those in danger of falling through the cracks - Calleja, Colin; Attard Tonna, Michelle; Busuttil, Leonard (Formazione & insegnamento, 2022)
This study presents five themes which were highlighted by Maltese educators and parents when reflecting on their experience of sustaining the education of their students and children during the COVID-19 pandemic. By capturing these voices, the study seeks to gain insight into how these educators and parents reflected on their practice and daily experiences and how this has impinged on the educational experience of the students.